Consumer Behavior in Advancing Circular Economy Practices at Dapur Tara Flores - Darma, I Made Krystya; Chang, Liv Artha; Wempi, J. A. (Communicare : Journal of Communication Studies, 2025)
This study examines how circular economy practices are communicated and implemented by Dapur Tara, a community-based culinary enterprise in Liang Ndara Village, East Nusa Tenggara. Motivated by the Indonesian government’s agenda for a sustainable economic recovery, the research addresses the gap between national circular-economy strategies and their adoption at the grassroots level. Employing a qualitative case study design under a constructivist paradigm, data were collected through direct observation and in-depth interviews with the business owner and selected consumers. The findings demonstrate that Dapur Tara operationalizes circular principles through practices such as organic sourcing, eco-conscious waste management, and the use of reusable packaging, while simultaneously embedding these practices into its marketing communication strategies. Communication is delivered through interactive, culturally rooted experiences and digital platforms, effectively resonating with environmentally conscious tourists. The study highlights the potential of experiential and participatory communication to influence sustainable consumer behavior and strengthen the impact of circular economy models at the local level, while also identifying infrastructure limitations as key challenges to scalability.